Qualitative Studies in Quality of Life
XIII, 240 p.
Keywords: This volume explores the use and relevance of qualitative methods for the study of quality of life. It analyzes the role of qualitative researcher and the role of the context and the culture in quality of life studies. It presents the use of qualitative methods in real projects carried out in specific fields: geography, health, community studies, labor life and yoga. Finally, the book proposes the use of mixed methods that are considered as the third methodological approach in social research. The main purpose of using qualitative methods is to understand what it means for participants to be involved in certain events, situations and actions. Such methods help understand the context in which participants act and the influence of that context on their actions. The decision to use a particular methodology implies a philosophic, theoretical and political decision. Qualitative methodology constitutes an approach that is essential for understanding people’s experiences of well-being and discovering new issues related to quality of life.